Association of ACL Laxity Tests with Arthroscopic Findings in Chronic ACL and PCL Deficient Knees - Sazali, S.; Rusdi, A.; Siti, H. T. (The Surgery Journal, 2018)
An anterior cruciate ligament (ACL) injury may be diagnosed by clinical examination and radiological investigation using magnetic resonance imaging or by arthroscopy.1,2 Based on our experience, the ACL tear in concomitant chronic ACL and posterior cruciate ligament (PCL) deficient knees may produce knee laxity, which is more difficult to assess on clinical examination, which in turn may affect the management algorithm of the patient. Our hypothesis is that, in a concomitant chronic ACL and PCL injury, posterior capsular contracture and abnormal reattachment of torn ACL will result in less clinical and subjective laxity, preoperatively. The aim of this study is to review a cohort of patients who had undergone PCL reconstructive surgery and compare the preoperative clinical assessments with and without anesthesia with arthroscopic finding of ACL. This is to assess the accuracy and reliability of clinical ACL laxity tests in detecting ACL tear in chronic ACL and PCL injury.
Keywords: chronic ACL and PCL injury; ACL laxity tests; association between ACL laxity tests and arthroscopy findings